2022
DOI: 10.3390/ma15113872
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mechanical Properties Related to Fiber Length of Closed-Loop-Recycled Offcuts of a Thermoplastic Fiber Composites (Organo Sheets)

Abstract: Increasing demand for energy-efficient means of transport has steadily intensified the trend towards lightweight components. Thermoplastic glass fiber composites (organo sheets) play a major role in the production of functional automotive components. Organo sheets are cut, shaped and functionalized by injection molding to produce hybrid components, such as those used in car door modules. The cutting process produces a considerable amount of production waste, which has thus far been thermally recycled. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…The study revealed that offcut layup barely influences the fiber length distribution compared with the flake size. Hummel et al 30 analyzed the mechanical properties related to fiber length of closed-loop-recycled offcuts of organo-sheet thermoplastic fiber composites. These were processed via injection molding to produce hybrid components such as car door modules.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that offcut layup barely influences the fiber length distribution compared with the flake size. Hummel et al 30 analyzed the mechanical properties related to fiber length of closed-loop-recycled offcuts of organo-sheet thermoplastic fiber composites. These were processed via injection molding to produce hybrid components such as car door modules.…”
Section: Introductionmentioning
confidence: 99%